2012
DOI: 10.1371/journal.pone.0030791
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Milk-Feeding Type and Genetic Risk of Developing Coeliac Disease on Intestinal Microbiota of Infants: The PROFICEL Study

Abstract: Interactions between environmental factors and predisposing genes could be involved in the development of coeliac disease (CD). This study has assessed whether milk-feeding type and HLA-genotype influence the intestinal microbiota composition of infants with a family history of CD. The study included 164 healthy newborns, with at least one first-degree relative with CD, classified according to their HLA-DQ genotype by PCR-SSP DQB1 and DQA1 typing. Faecal microbiota was analysed by quantitative PCR at 7 days, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 32 publications
4
124
0
1
Order By: Relevance
“…7 Here, using species-specific primers, we have analysed the prevalence of two potentially pathogenic species of the Clostridium genus. The increased prevalence of C. perfringens found at 7 days, 1 month and 4 months of age in the formula-fed infants of our cohort is in agreement with previous studies reporting that formula feeding promoted the presence of C. perfringens .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7 Here, using species-specific primers, we have analysed the prevalence of two potentially pathogenic species of the Clostridium genus. The increased prevalence of C. perfringens found at 7 days, 1 month and 4 months of age in the formula-fed infants of our cohort is in agreement with previous studies reporting that formula feeding promoted the presence of C. perfringens .…”
Section: Discussionmentioning
confidence: 99%
“…7 , 8 In particular, we described that breast-fed infants with a high genetic risk (HLA-DQ2) of developing CD had reductions in Bifidobacterium spp., a feature that theoretically could be related to the development of the disease in the later life. 7 , 8 Besides, we observed that infants with a high genetic risk (HLA-DQ2) had a higher relative abundance of Proteobacteria, and of unclassified Enterobacteriaceae. 8 However, all the preceding studies were taxonomy-based, and the pathogenic potential of the increased abundance of the family Enterobacteriaceae remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations